Perception of ECE-TEP Students in Deepening Tenses through UPI Serang’s MBKM English Credential Camp Program - Siti Dela Soflianti; Herli Salim; Roby Naufal Arzaqi (Perkumpulan Pengelola Jurnal (PPJ) PAUD Indonesia, 2023)
This research aims to explore the perspectives of ECE-TEP students regarding the deepening of tenses through the MBKM English Credential Camp program at UPI Serang. The challenges of education in the modern 21st century push ECE-TEP students to possess English communication skills. This is important because English is an international language. The use of English tenses by ECE-TEP students often requires appropriate understanding and training. The ECC program is an integrated and holistic solution to enhance the use of tenses by ECE-TEP students. This research employs a qualitative descriptive approach with a case study. The primary data sources are direct questionnaires, audio recorders, and secondary data in the form of MBKM ECC program documents. Data analysis was conducted through four stages: data collection, data transcription, data categorization, and drawing conclusions. The research subjects consist of three individuals who are students of the ECC program. Participants are selected based on their academic performance in the program. The research findings indicate that the ECC program significantly contributes to improving the understanding of tenses among ECE-TEP students. This program is effective in preparing students to face the challenges of the 21st century through deepening improving their English language skills.